2022
DOI: 10.1021/acs.analchem.2c01188
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optical Detection of Multiple Bacterial Species Using Nanometer-Scaled Metal–Organic Hybrids

Abstract: This paper describes a simple strategy to identify bacteria using the optical properties of the nanohybrid structures (NHs) of polymer-coated metal nanoparticles (NPs). NHs, in which many small NPs are encapsulated in polyaniline particles, are useful optical labels because they produce strong scattered light. The light-scattering characteristics of NHs are strongly dependent on the constituent metal elements of NPs. Gold NHs (AuNHs), silver NHs (AgNHs), and copper NHs (CuNHs) produce white, reddish, and bluis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These results demonstrate that the NH size is correlated with the size of the metal NPs. Considering the reduction potentials of the metal species used for NH production, it has been reported that AuCl 4 – ( E ○ =1.0 V vs SHE) is more easily reduced than Ag + ( E ○ =0.80 V) and Cu 2+ ( E ○ =0.34 V) . The reduction potentials of metal ions and the oxidation potentials of monomers are considered important factors in NH formation in the nanoreaction field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that the NH size is correlated with the size of the metal NPs. Considering the reduction potentials of the metal species used for NH production, it has been reported that AuCl 4 – ( E ○ =1.0 V vs SHE) is more easily reduced than Ag + ( E ○ =0.80 V) and Cu 2+ ( E ○ =0.34 V) . The reduction potentials of metal ions and the oxidation potentials of monomers are considered important factors in NH formation in the nanoreaction field.…”
Section: Resultsmentioning
confidence: 99%
“…− (E ○ =1.0 V vs SHE) is more easily reduced than Ag + (E ○ =0.80 V) and Cu 2+ (E ○ =0.34 V). 45 The reduction potentials of metal ions and the oxidation potentials of monomers are considered important factors in NH formation in the nanoreaction field. However, no clear correlation was observed between the reduction potential of the metal ions and the growth of metal NPs in the polymer matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Bacterial cultures and all experiments were developed and managed in a Biosafety Level 2 laboratory in accordance with the appropriate safety regulations (WHO Laboratory Biosafety Manual). 6,7 The bacterial strain was cultured in an agar growth medium (E-MC35, Eiken Chemical, Japan) at 310 K for 18 h. A single colony was selected, placed in a liquid growth medium (5.0 mL), and incubated at 310 K for 6 h. The precipitate was dispersed in sterile ultrapure water and the E. coli K12 suspension concentration was adjusted to 3.6 © 10 11 CFU mL ¹1 .…”
Section: Methodsmentioning
confidence: 99%
“…4,5 In recent years, many studies have reported on the development of biosensors using novel materials and technologies. For highly sensitive and rapid detection of pathogenic bacteria, biosensors based on physical or chemical signals, such as light scattering, [6][7][8][9] fluorescence, 10,11 electrochemistry, [12][13][14][15] and piezoelectricity, 16 have been developed. In particular, electrochemical biosensors are particularly useful in fields where on-site testing is required because of their high sensitivity, rapid measurement, and ease of device miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…The common approach for building LSPR-based sensors relies on the scattering signal assay that detects the intensity and color of the scattering light of nanoparticles, which can be efficiently observed using dark-field microscopy (DFM). With the advantages of high sensitivity, high signal-to-noise, and high spatial and temporal resolution, DFM has been broadly used for quantitative analysis, , dynamic monitoring, , biological sensing, and material performance evaluation by observing the color change of the scattering light of nanoparticles in DFM images. However, due to the heterogeneity of the sample, the scattering information on a single nanoparticle cannot reflect the real distribution of the whole situation accurately.…”
Section: Introductionmentioning
confidence: 99%